An Analysis the Role of Extracurricular Sports in Building a Positive School Image - Mudzakir, Muhammad Fahmi; Juliantine, Tite; Carsiwan, Carsiwan; Yulianto, Ari Gana (Journal of Educational Sciences, 2025)
Sports extracurricular activities play a vital role in student development and enhancing school reputation. This research analyzes factors influencing the role of sports extracurricular activities in building a positive school image. This study employs a systematic literature review approach to examine research trends from 2014 to 2024. Data were collected from the Scopus, Web of Science, and Google Scholar databases, yielding 125 articles based on specific keywords for analysis. The analysis covers several key themes, including The Correlation Between Extracurricular Participation and Academic Achievement, The Role of Infrastructure and Institutional Support, Extracurricular Activities as a Strategy for Enhancing Institutional Reputation, and Effective Management and Character Development. Studies show a positive correlation between student involvement in extracurricular activities and academic achievement, but confounding factors need to be considered. Facility availability, institutional support, effective management, and branding strategies are key factors in program success. Sports extracurricular activities have significant potential in building a positive school image. Investing in the development of these programs is a strategic step in improving the overall quality of education.